ANALISIS TINGKAT KETERTARIKAN KONSUMEN TERHADAP CRAFT FASHION ATAU FASHION GAYA ETNIK KONTEMPORER - Finardi, Muhammad Fayyadh (Jurnal Ilmiah Manajemen & Bisnis, 2020)
The research was titled "Consumer interest Rate analysis of Craft Fashion or contemporary ethnic style Fashion" aims to know the interest of consumer to buy Craft Fashion or contemporary ethnic style Fashion. This research is a kind of qualitative descriptive research to get an overview of the topics of research researched. Data retrieval is conducted by spreading questionnaires to 32 respondents who meet the criteria. The development of Indonesian fashion today tends to lead to Western style. In fact, Indonesia could become the world fashion mecca, by providing innovations for the fashion industry to make fashion craft that combines today's fashion with a mixture of unique and luxurious Indonesian fabrics, but still many are not aware of it. The results showed that there were still many who did not know about Craft Fashion, but after given a brief explanation on the topic many respondents who answered interested to use it. So, it can be concluded that Indonesian consumers are still less educated about the Craft Fashion itself.